Resilience of Islamic banks in Yemen: an analysis of monetary and financial performance - Saleh, Abdulmajid Obaid Hasan; Alrashedi, Mohammed Yahya Alrashedi (2024)
Islamic banks in Yemen showed impressive financial growth from January to May 2024, with total assets increasing to YER12.23 trillion (US$6.41 billion), reflecting their strong asset management capabilities and growing trust from customers. Foreign assets also rose consistently, reaching YER3.88 trillion (US$2.03 billion), indicating sustained confidence from international investors in the stability of these banks. The expansion of loans and advances to YER1.99 trillion (US$1.04 billion) underscores the banks’ pivotal roles in supporting the private sector and fostering economic activity through Shariah-compliant financing solutions.